Les entreprises de prostitution commerciale : les commerces éphémères des marchés illicites - Leguerrier, Yves (Criminologie, 1989)
This article concerns the commercial prostitution that was operating in the Montreal region from 1981 to 1985. An analysis of the police archives and the classified advertisements made it possible to reconstitute the decisions a criminal who wants to get into this market has to make with regard to the opportunities available and the specific requirements of his milieu (social and police-related). One of the major conclusions of this article is the transient structural nature of ventures in commercial prostitution. The results could be evidence of the temporary nature and instability of the criminal opportunities themselves.